Biomarker release after percutaneous coronary intervention in patients without established myocardial infarction as assessed by cardiac magnetic resonance with late gadolinium enhancement. Issue 1 (2nd June 2017) - Vieira de Melo, Rodrigo Morel; Hueb, Whady; Nomura, Cesar Higa; Ribeiro da Silva, Expedito Eustáquio; Villa, Alexandre Volney; Oikawa, Fernando Teiichi Costa; da Costa, Leandro Menezes Alves; Rezende, Paulo Cury; Garzillo, Cibele Larrosa; Lima, Eduardo Gomes; Franchini Ramires, Jose Antonio; Kalil Filho, Roberto
Abstract : Objectives: This study aimed to evaluate the amount and pattern of cardiac biomarker release after elective percutaneous coronary intervention (PCI) in patients without evidence of a new myocardial infarction (MI) after the procedure as assessed by cardiac magnetic resonance (CMR) with late gadolinium enhancement (LGE). Background: The release of myocardial necrosis biomarkers after PCI frequently occurs. However, the correlation between biomarker release and the diagnosis of procedure‐related MI type 4a has been controversial. Methods: Patients with normal baseline cardiac biomarkers who were referred for elective PCI were prospectively included. CMR with LGE was performed in all of the patients before and after the intervention. Measurements of troponin I (TnI) and creatine kinase MB fraction (CK‐MB) were systematically performed before and after the procedure. Patients with a new LGE on the post‐procedure CMR were excluded. Results: Of the 56 patients with no evidence of a procedure‐related MI as assessed by CMR after the PCI, 48 (85.1%) exhibited an elevation of TnI above the 99th percentile. In 32 patients (57.1%), the peak was greater than five times this limit. Additionally, 17 patients (30.4%) had a CK‐MB peak above the 99th percentile limit, but this peak was greater than five times the 99th percentile in only two patients (3.6%). The median peak release of TnI was 0.290 (0.061–1.09) ng/mL, which was 7.25‐fold higher than the 99th percentile. Conclusions: In contrast to CK‐MB, an abnormal release of TnI often occurs after an elective PCI procedure, despite the absence of a new LGE on CMR.